Implementasi Metode Permainan Bahasa untuk Siswa Sekolah Dasar Sebagai Upaya Pembentukan Karakter Sosial dan Humanis - Harbelubun, Yohanna Claudia Dhian Ariani (GERAM: Gerakan Aktif Menulis, 2023)
Character formation can be integrated not only into learning materials but also into the learning methods that we choose and use. The game method is also a method that we can design for conveying material as well as building and shaping children's character. Especially for elementary school students, the game method is definitely liked by children. If psychologically the child is happy in learning, then knowledge and character values can be easily accepted by the child, which also makes it easier for the teacher to direct the social values and positive values of each game. This article examines the socio-epistemological philosophy of the game method in elementary school. This research was conducted using descriptive qualitative methods, interviews, and FGD techniques. The participants in this study were elementary school teachers in Jakarta. The language game method studied is a game that has an impact on learning, both to improve results and to shape the social character of students. The purpose of this study is to further examine the sociological impact of the game method. It is this sociological impact that will shape students from elementary school into people who are humane and have social character.